Broad band solar cell absorber based on double-ring coupled disk resonator structure: from visible to mid infrared. (1st April 2023) - Meng, Qiqi; Chen, Fang; Cheng, Shubo; Yang, Wenxing; Yi, Zao
Abstract: In this paper, a broad band absorber based on a double-ring coupled disk resonator periodic structure, which can work in the visible and mid infrared range, is proposed and investigated. Results show the absorbance is large than 92.4% in the range of 300 nm–4096 nm, and the average absorption is about 97.4% from the visible to mid-infrared bands. Besides, the proposed absorber is wide angle acceptance, background refractive index (RI), and polarization state insensitive. The absorption mechanisms are analyzed and found that it mainly originated from the dielectric lossy property in short-wavelength and gap plasmonic resonances in long-wavelength. It is believed the proposed absorber can find potential applications in the fields of solar cell devices, thermal emitters, and plasmonic imaging.